Chelating functional group attached to carbon nanotubes prepared for performance enhancement of vanadium redox flow battery. Issue 40 (2nd October 2017) - Noh, Chanho; Moon, Seongeun; Chung, Yongjin; Kwon, Yongchai
Abstract : When hydroxamic acid functionalized carbon nanotube (CNT) catalyst is adopted for VO 2+ /VO 2+ reaction, VRFB performance is best. It is due to the chelation ability of hydroxamic acid. With the role as chelating agent, hydroxamic acid properly interacts with VO 2+ and VO 2+, promoting their redox reactions. Abstract : A hydroxamic acid functionalized carbon nanotube (HAA-CNT) catalyst is prepared to determine its effect on VO 2+ /VO2 + and V 2+ /V 3+ redox reactions and on the performance of a vanadium redox flow battery (VRFB), while its catalytic activity and VRFB performance are compared with those of pure CNTs and carboxylic acid functionalized CNT (CA-CNT) catalysts. According to the cyclic voltammetry measurements, HAA-CNT shows a better catalytic activity and reaction reversibility for vanadium redox reactions than CNT and CA-CNT because of the chelation ability of the HAA included in the HAA-CNT. With the role of chelating agent, the HAA group interacts well with vanadium ions, promoting their redox reactions. In particular, the HAA-CNT is more effective for the VO 2+ /VO2 + reaction than the V 2+ /V 3+ reaction because of the larger number of oxygen atoms considered as active sites for the VO 2+ /VO2 + reaction. The role promoting VO 2+ /VO 2+ reaction is confirmed by measuring charge transfer resistance efficiencies of a single cell VRFB. The chemical structure of the HAA-CNT is determined using X-ray photoelectron spectroscopy (XPS). Eventually, when the HAA-CNT is used as a positive electrode for the VO 2+ /VO2 + reaction, the performance of single cell VRFB is best.